Was the media campaign that supported Australia's new pictorial cigarette warning labels and plain packaging policy associated with more attention to and talking about warning labels?. (October 2015) - Nagelhout, Gera E.; Osman, Amira; Yong, Hua-Hie; Huang, Li-Ling; Borland, Ron; Thrasher, James F.
Abstract: Background: Population-level interventions can possibly enhance each other's effects when they are implemented simultaneously. When the plain packaging policy was implemented in Australia, pictorial health warning labels (HWLs) on cigarette packages were also updated and a national mass media campaign was aired. This study examined whether smokers who recalled the media campaign reported more attention to and talking about HWLs. Methods: Longitudinal survey data was obtained among Australian adult smokers, aged 18 years and older, from an online consumer panel. One survey wave was conducted before (September 2012) and two waves were conducted after (January 2013 and May 2013) the interventions. The sample was replenished to maintain a sample size of 1000 participants at each wave. Generalized Estimating Equations analyses were performed. Results: Compared to wave 1, attention to HWLs increased at wave 2 ( b  = 0.32, SE = 0.06, p  < 0.001), but not at wave 3 ( b  = 0.10, SE = 0.08, p  = 0.198). Talking about HWLs increased over time (IRR = 1.82, 95% CI = 1.58–2.09 and IRR = 1.25, 95% CI = 1.05–1.47, at wave 2 and wave 3 respectively). Campaign recall was significantly associated with more attention to HWLs ( b  = 0.29, SE = 0.05, p  < 0.001) and with more talking about HWLs (IRR = 1.17, 95% CI = 1.06–1.29) with similar effects across waves 2 and 3. Conclusions: Recall of the campaign was associated with more attention to and talking about HWLs. When adjusting for campaign recall, there was still an increasing trend in attention and talking. This suggests that the media campaign and the new packaging and labeling policies had independent and positive effects on attention to and talking about HWLs. Highlights: Australia implemented a plain packaging policy for cigarette packages in 2012. Pictorial health warning labels (HWLs) on cigarette packages were also updated. A national mass media campaign was aired that complemented the labeling policies. Recall of the campaign was associated with more attention to and talking about HWLs. Adjusting for campaign recall, there was still an increase in attention and talking.